2016
DOI: 10.1155/2016/4837270
|View full text |Cite
|
Sign up to set email alerts
|

Adding Water to the Mill: Olmesartan-Induced Collagenous Sprue—A Case Report and Brief Literature Review

Abstract: Collagenous sprue (CS) is a distinct clinicopathological disorder histologically defined by a thickened subepithelial band (Freeman, 2011). It is a rare condition which has been recently observed in a significant proportion of sprue-like enteropathy associated with olmesartan, a novel entity described by Rubio-Tapia et al. in 2012. CS is historically associated with a poor prognosis (Marthey et al., 2014). However, histological and clinical improvements have been described in most studies with concomitant usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 4 publications
(6 reference statements)
0
20
0
1
Order By: Relevance
“…A severe form of intestinal injury with chronic diarrhea due to olmesartan was first described by Rubio-Tapia et al in 2012 [2]. Numerous other reports of olmesartan-associated enteropathy have since appeared in the literature, several of which during the last few years [4][5][6][7][8][9][10][11][12][13][14][15], suggesting that this clinical entity is eventually being more and more recognized. In fact, in 2013, the Food and Drug Administration (FDA) approved label changes to include updated data about the association of olmesartan with sprue-like enteropathy [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A severe form of intestinal injury with chronic diarrhea due to olmesartan was first described by Rubio-Tapia et al in 2012 [2]. Numerous other reports of olmesartan-associated enteropathy have since appeared in the literature, several of which during the last few years [4][5][6][7][8][9][10][11][12][13][14][15], suggesting that this clinical entity is eventually being more and more recognized. In fact, in 2013, the Food and Drug Administration (FDA) approved label changes to include updated data about the association of olmesartan with sprue-like enteropathy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory evaluation is usually indicative of malabsorption with normocytic anemia, hypoalbuminemia and multiple electrolyte abnormalities. Dehydration and acute renal failure are the most frequent causes of hospitalization, even in the Intensive Care Unit (ICU) [6,15]. Other unusual cases of this entity include colonic perforation [24], Wernicke-Korsakoff syndrome due to vitamin B1 malabsorption with minimal gastrointestinal symptoms [25], nonalcoholic steatohepatitis [26] and simultaneous olmesartan-associated uveitis with enteropathy [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best-known severe adverse event associated with olmesartan is sprue-like enteropathy, according to several case reports and research articles [ 85 – 90 ]. Rubio-Tapia et al firstly reported that 22 olmesartan recipients who suffered from chronic diarrhea could recover from the syndrome after stopping olmesartan therapy [ 91 ].…”
Section: Methodsmentioning
confidence: 99%
“…The etiology of collagenous gastroenteritis is unknown but is suspected to be immune-mediated and may be associated with certain medications including the antihypertensive drug olmesartan, an angiotensin II receptor antagonist [ 2 ]. Several reports in the literature describe cases of olmesartan-associated collagenous duodenitis/sprue [ 3 5 ] with fewer reports of olmesartan-associated collagenous gastritis [ 3 , 6 ] and only rare reports involving both the stomach and small bowel [ 3 ]. We herein report a case of olmesartan-associated collagenous gastroduodenitis that was complicated by acute gastrointestinal bleeding during endoscopy.…”
Section: Introductionmentioning
confidence: 99%